SAT0027 Baseline Factors That PREDICT High Blys Levels (≥2 NG/ML) in Patients with Systemic Lupus Erythematosus: Data from the BLISS Trials. (10th June 2014) - Roth, D.; Thompson, A.; Tang, T.; Hammer, A.; Molta, C.
Abstract : Background: Post-hoc analyses from the BLISS trials demonstrated that patients with high baseline B-lymphocyte stimulator (BLyS) levels (≥2 ng/ml) had an increased risk of a clinically meaningful flare over 1 year. 1 Objectives: Given that BLyS levels are not routinely collected in clinical practice, further analyses were conducted to identify clinical variables that may be predictive of high BLyS levels. Methods: Data from BLISS-52 (NCT00424476 ) and BLISS-76 (NCT00410384 ) were pooled (GSK200619). All randomised subjects with baseline BLyS levels were included. A logistic regression analysis was performed. A univariate logistic regression was first employed to identify a subset of baseline factors (e.g. demographic, disease activity, laboratory, biomarker and systemic lupus erythematosus [SLE] medication usage) predictive of high baseline BLyS levels. Only baseline factors that were significant at the 0.05 level entered the final logistic regression as covariates. Results: A total of 380 out of 1664 (22.8%) subjects had high baseline BLyS levels (≥2 ng/ml). Most subjects were female (n=344, 90.5%); mean age was 36 (11.0 SD) years, and mean SELENA-SLEDAI score was 10.8 (4.29 SD). Significant baseline predictors of high baseline BLyS levels included positive anti-Smith (≥15 U/ml; χ 2 =17.04, p<0.01), low C3 (χ 2 =4.81, p<0.05), anti-dsDNA (>200 IU/ml; χ 2 =20.41, p<0.01) and anti-dsDNA (80–200 IU/ml; χ 2 =5.85, p<0.05), use of immunosuppressant medication (χ 2 =27.39, p<0.01), proteinuria (≥0.5 g/24 h; χ 2 =18.91, p<0.01) and elevated C-reactive protein (>3 mg/L; χ 2 =51.61, p<0.01). Conclusions: Positive anti-Smith, low C3, positive anti-dsDNA, immunosuppressant usage, proteinuria and elevated C-reactive protein were predictors of high BLyS levels. Identifying routinely collected clinical variables predictive of high BLyS levels, which are associated with moderate-to-severe flare and high disease activity, is useful in the ongoing management of SLE. Disclosure of Interest: D. Roth Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Thompson Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, T. Tang Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Hammer Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Molta Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline DOI: 10.1136/annrheumdis-2014-eular.4975